Medication Choices in Children With Tic Disorders in Mainland China, Macao, Hong Kong, and Taiwan: Perspectives of Guardians and Physicians - Yang, Chunsong; Yang, Yaya; Zhang, Lingli; Zhao, Li (Frontiers in Pharmacology, 2022)
Objective: Survey pediatricians and guardians of children with tic disorder on medication needs and choices. Methods: We designed a cross-sectional survey for pediatricians in mainland China, Hong Kong, Macao, and Taiwan, as well as for the guardians of patients with tic disorder from West China Second University Hospital. We collected and analyzed information on clinicians’ medical behavior and medication choices and on guardians’ knowledge of tic disorder, medical treatment behaviors, and medication choices and needs. Results: We collected responses from 242 physicians and 610 guardians. For patients with tic disorder and without comorbidities, the first-line drugs selected by physicians were tiapride (60.74%), clonidine (32.64%), haloperidol (25.62%), aripiprazole (16.53%), and sulpiride (12.4%). Physicians reported making medication choices by considerations such as clinical guidelines, clinical efficacy, a low incidence of adverse drug reactions, sufficient clinical research evidence, convenient dosage forms, and patient adherence. Guardians reported making medication choices by considerations such as a low incidence of adverse drug reactions, physician recommendations, clinical efficacy, dose, dosage forms, and the convenience and steadiness of obtaining the medication. However, guardians exhibited insufficient knowledge of tic disorder and treatment options. Conclusions: Physicians and patient guardians differ in their considerations when selecting medications, highlighting a gap in optimizing treatment.